Unique hierarchical porous carbon nanosheet network for supercapacitors: Ultra-long cycling stability and enhanced electroactivity of oxygen at high temperature. (1st January 2023) - Qiu, Chuang; Zuo, Mingyuan; Qiu, Daping; Cao, Jiakai; Jia, Xuye; Li, Yifan; Liu, Changhe; Chen, Nianhua; Chen, Xiaohong; Li, Min
Abstract: Porous carbon-based supercapacitors (SCs) are promising electrochemical energy storage devices. However, the unreasonable design of porous carbon leads to poor energy density and unsatisfactory high-temperature cycling stability of SCs. Herein, we synthesize a hierarchical porous carbon nanosheet network by combining self-templated pyrolysis and KOH activation strategies. This carbon nanosheet network exhibits an extremely large active ion-accessible pore volume (V0.76–6 nm =1.654 m 3 g −1 ) and a considerable supermesopore volume (V6–50nm 0.413 m 3 g −1 ), which provide abundant active sites and fast diffusion channels for electrolyte ions, respectively. Futhermore, the enhanced electroactivity of oxygen at high temperature is demonstrated, which provides additional active sites. Inspiringly, the as-constructed EMIMBF4 -based SCs can be well serviced at the high temperature of 80 °C with ultra-high energy/power density of 122.23 Wh kg −1 /40.6 kW kg −1 and superior durability (81.1% retention after 8000 cycles at 20 A g −1 ). This work provides insights into the effect of temperature on the electroactivity of oxygen, as well as the construction of porous carbon-based high-temperature SCs with desired performance metrics. Graphical abstract: Image, graphical abstract